Global Awareness Themes in English Senior High School Textbook - Ratnaningsih, Herin (Nexus Publishing, 2024)
This study explores the extent of global awareness themes in Senior High School English textbooks in Merdeka Curriculum. With the growing importance of global interconnectedness, it is essential to assess how English Senior High School textbooks address global issues. By employing a comprehensive content analysis method, this study examines three Senior High School English Textbooks to identify the global awareness topics incorporated into the curriculum. Findings of this study show that four global awareness themes are included in all textbooks: (i) global system (economics, environment, health, sports, finance, education, and peace; (ii) diverse human values, (iii) global issues and (iv) world cultures. The distributions of the global awareness themes in English textbook grade XII are more comprehensive than in grade X and XI. This research contributes to understanding textbooks' role in shaping global awareness among Indonesian students.